2018
DOI: 10.1002/hep.29631
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between alcohol consumption and metabolic syndrome in predicting severe liver disease in the general population

Abstract: Multiple components of the metabolic syndrome independently affected the risk for severe liver disease. Alcohol was significant even when average alcohol consumption was within the limits currently defining nonalcoholic fatty liver disease. (Hepatology 2018;67:2141-2149).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
188
3
4

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 200 publications
(207 citation statements)
references
References 34 publications
(78 reference statements)
12
188
3
4
Order By: Relevance
“…However, Aberg et al . reported that mild‐to‐moderate alcohol consumption is associated with an increase in liver‐related events, including decompensated liver cirrhosis . This result differs from the present result, and this might be explained by the difference in the prevalence of individuals with metabolic syndrome.…”
Section: Discussioncontrasting
confidence: 99%
“…However, Aberg et al . reported that mild‐to‐moderate alcohol consumption is associated with an increase in liver‐related events, including decompensated liver cirrhosis . This result differs from the present result, and this might be explained by the difference in the prevalence of individuals with metabolic syndrome.…”
Section: Discussioncontrasting
confidence: 99%
“…Unfortunately, patients with liver cirrhosis are often referred after cirrhosis is well established [11], especially in case of alcohol use disorders. Despite this, there are steps that can be taken to prevent progression of cirrhosis such as more attention to life style, since being overweight, having diabetes and excess alcohol intake share pathways for the pathogenesis of chronic liver disease, cirrhosis and portal hypertension [12].…”
Section: Treatment Of Cirrhosis Aetiologymentioning
confidence: 99%
“…High BMI is a risk factor for ALD 20 and has even a supra-additive effect on the risk of ALD. 24 Our model recognized WHR as an independent risk factor. 22 Overweight increases the risk of hepatocellular carcinoma, as well.…”
Section: Risk Factors For Advanced Liver Diseasementioning
confidence: 88%